The era of water-enabled electricity generation from graphene. Issue 25 (3rd June 2016) - Tang, Qunwei; Yang, Peizhi
Abstract : Water-enabled electricity generation from graphene based materials is a rising field and has been considered to be promising for application-specific requirements. By summarizing the principles behind the electrical signal outputs, the architecture optimization of the corresponding devices as well as performance maximization can be realized. Abstract : With the abundance of traditional energy conversion devices such as solar cells, fuel cells, lithium batteries and supercapacitors, the integration of graphene with water is an increasingly used method for promising electricity generation (including current, voltage, and power) in the last few years. We present here a review on the significant advances in tailored graphene-based materials for unprecedented power generation by flowing, raining, waving, or penetrating water. This article highlights the potential principles behind the electric signals to guide the design and synthesis of graphene-based systems for emerging power generation methods. Use of the peculiar performances of creating electric signals, the methodologies of constructing advanced devices using these graphene-based electrodes for real applications and identification of the challenges facing the water-enabled graphene for electricity generation are also discussed.